2021
DOI: 10.3389/fpsyt.2021.717877
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Behavioural and Self-Reported Cognitive Empathy Deficits in Adolescents With Autism Spectrum Disorders and Adolescents With Behavioural Difficulties

Abstract: Deficits in empathy have been considered hallmarks in individuals with autism spectrum disorders (ASD) but are also considered to underlie antisocial behaviour associated with individuals with callous unemotional traits (CU). Research has suggested that individuals with autism spectrum disorders show more difficulties with cognitive empathy, and that individuals diagnosed with behaviours difficulties, characterised by CU traits and antisocial behaviour, demonstrate low affective empathy. In the current manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 97 publications
(147 reference statements)
1
12
0
Order By: Relevance
“…The potentially overlapping empathy deficits displayed by the group of youths with ASD and those with CD results would be in line with the overlapping aggressive, antisocial, and disruptive symptoms observed in ASD and CD, which were also associated with empathy deficits in previous studies (Frick et al, 2013;Kaat & Lecavalier, 2013). For the ASD group, global empathy deficits were observed, in line with the existing evidence of deficits in CE (K. Rogers et al, 2007;Schwenck et al, 2012;Vilas et al, 2021), but also in abilities that need both AE and CE (Lombardo et al, 2010) such as self-other distinction. Against expectations, CD youths only showed CE deficits in the parent-report and no deficits in the self-report, which might suggest differences between self-perceived and externally observed empathy abilities.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The potentially overlapping empathy deficits displayed by the group of youths with ASD and those with CD results would be in line with the overlapping aggressive, antisocial, and disruptive symptoms observed in ASD and CD, which were also associated with empathy deficits in previous studies (Frick et al, 2013;Kaat & Lecavalier, 2013). For the ASD group, global empathy deficits were observed, in line with the existing evidence of deficits in CE (K. Rogers et al, 2007;Schwenck et al, 2012;Vilas et al, 2021), but also in abilities that need both AE and CE (Lombardo et al, 2010) such as self-other distinction. Against expectations, CD youths only showed CE deficits in the parent-report and no deficits in the self-report, which might suggest differences between self-perceived and externally observed empathy abilities.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the inclusion of CU traits in the computational models reduced the relevance of the AE but not CE deficits for the ASD group, suggestive of a potential differential impact of CU traits on empathy deficits on each disorder. These findings would help to understand those of previous studies where deficits in pure CE processes were found only in ASD samples and not in youth with high levels of CU traits (Jones et al, 2010;O'Nions et al, 2014;Schwenck et al, 2012;Vilas et al, 2021). This might further suggest that CE T A B L E 5 Spatial centers of gravity depicting the shared peak clusters of the region of interest analysis negatively associated with callousunemotional traits.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Autistic children are described as being indifferent to other people's distress and less likely to offer comfort to others in distress. Based on findings from self‐ and parent‐report scales and clinical observations, autistic adolescents (mean age of 15 years) tend to show difficulties in cognitive empathy and empathic concern (Vilas et al, 2021). However, in studies using skin conductance, pupillometry, and brain activations to measure emotional empathy, an unconscious and automatic process, autistic adults showed more complex patterns of empathy (e.g., Gu et al, 2015).…”
Section: The Hyperarousal Accountmentioning
confidence: 99%